أثر خصائص لجنة المراجعة على العلاقة بين توقيت إصدار تقرير المراجعة والكفاءة الاستثمارية للشركات: دراسة تطبيقية - أبو الخير، محمد حارس محمد طه (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
تعد الدراسة الحالية بمثابة إضافة علمية لأدبيات الفكر المحاسبي من خلال تقديمها أدلة جديدة في بيئة الأعمال المصرية حول أثر خصائص لجنة المراجعة على العلاقة بين توقيت إصدار تقرير المراجعة والكفاءة الاستثمارية للشركات. الهدف: قياس أثر خصائص لجنة المراجعة على العلاقة بين توقيت إصدار تقرير المراجعة والكفاءة الاستثمارية للشركات. التصميم والمنهجية: اعتمد الباحث على أسلوب تحليل المحتوى في فحص التقارير المالية لعينة مكونة من (58) شركة من الشركات المقيدة بالبورصة المصرية خلال الفترة من (2017-2023)، وقد بلغت مشاهدات العينة 305 مشاهدة بغرض اختبار فروض البحث. النتائج والتوصيات: تشير النتائج إلى وجود تأثير إيجابي معنوي لتوقيت إصدار تقرير المراجعة على الكفاءة الاستثمارية في ضوء خصائص لجنة المراجعة ويشير ذلك إلى قبول فروض البحث حيث نص الفرض الأول على "يؤثر توقيت إصدار تقرير المراجعة على الكفاءة الاستثمارية للشركات غير المالية المقيدة بالبورصة المصرية"، والفرض الثاني: "تؤثر خصائص لجنة المراجعة على العلاقة بين توقيت إصدار تقرير المراجعة والكفاءة الاستثمارية للشركات"، واستنادا إلى ذلك أوصى الباحث بمجموعة من التوصيات كان أهمها: توعية مجالس إدارات الشركات بأهمية الكفاءة الاستثمارية والعمل الدائم نحو الوقوف على المتغيرات التي يمكن أن تؤثر على تلك الكفاءة، كما أوصت الدراسة بزيادة عدد الأعضاء المستقلين في لجنة المراجعة للرفع من كفاءة وفعالية عمل اللجنة، والعمل على وضع تعريف محدد للخبرة المالية لدى أعضاء اللجنة لما له تأثير على تفعيل أعمال اللجنة وإرساء قواعد الحوكمة. الأصالة والإضافة العلمية: يعد البحث من الدراسات العربية الهامة التي تناولت أثر خصائص لجنة المراجعة على العلاقة بين توقيت إصدار تقرير المراجعة والكفاءة الاستثمارية للشركات، بالإضافة إلى تقديم دليل تطبيقي من البيئة المصرية في ضوء اهتمامات الجهات المعنية، وهو ما قد يساهم في دعم وتعزيز رؤية المحاسبة والمراجعة في هذا الشأن. The current study is considered a scientific addition to the literature of accounting thought by providing new evidence in the Egyptian business environment about the impact of the characteristics of the audit committee on the relationship between the timing of issuing the audit report and the investment efficiency of companies. objective: to measure the effect of the characteristics of the audit committee on the relationship between the timing of issuing the audit report and the investment efficiency of companies. design and methodology: the researcher relied on the content analysis method to examine the financial reports of a sample consisting of (58) companies listed on the Egyptian stock exchange during the period from (2017-2023). the sample views amounted to 305 views for the purpose of testing the research hypotheses. results and recommendations: the results indicate that there is a significant positive effect of the timing of issuing the audit report on investment efficiency in light of the characteristics of the audit committee. this indicates acceptance of the research hypotheses, as the first hypothesis stated: "the timing of issuing the audit report affects the investment efficiency of non-financial companies listed on the Egyptian stock exchange". the second hypothesis: "the characteristics of the audit committee affect the relationship between the timing of issuing the audit report and the investment efficiency of companies". based on that, the researcher recommended a set of recommendations, the most important of which were: raising companies’ boards of directors’ awareness of the importance of investment efficiency and constant work towards identifying the variables that can affect that. efficiency. the study also recommended increasing the number of independent members in the audit committee to increase the efficiency and effectiveness of the committee’s work, and working to develop a specific definition of the financial expertise of committee members, as it has an impact on activating the committee’s work and establishing governance rules. originality and scientific addition: the research is considered one of the important Arab studies that addressed the impact of the characteristics of the audit committee on the relationship between the timing of issuing the audit report and the investment efficiency of companies, in addition to providing practical evidence from the Egyptian environment in light of the interests of the concerned parties, which may contribute to supporting and enhancing the vision of accounting. and review in this regard.